Vibration Serviceability of Long Span Slender Floors - Matela, Mou Michael (Department of Civil Engineering, 2022)
The modern trend towards long slender floors has led to major vibration serviceability issues in building floors under rhythmic loading. This happens as a result of reduced natural frequencies and damping ratios due to reduced structural rigidity (Devin et al, 2015). Even though these vibrations do not lead to structural failure in most cases, they can often create such an excessive discomfort to the occupants that they render the structure unusable (Orvin et al, 2016). A serviceable long-span floor is a floor that does not only carry the permanent and imposed loads applied onto it, but one that is stiff enough to prevent excessive deflections as well as vibrations (Cement and Concrete Association of Australia, 2003). Common structural systems used for long span floors are plane trusses, space frames and space grids. These types of structures are generally lighter and stronger because individual members carry externally applied loads mainly through tension and compression which makes them more structurally efficient than solid-web girders which are subjected to flexure (Porwal et al, 2017). This research focusses on the vibration serviceability of long span floors subjected to rhythmic loads such as aerobics, dance-type loads or similar audience participation activities. The most important parameter in the design for vibration serviceability is the natural frequency and simplified methods in which it can be estimated for concrete floors supported on a steel frame or truss exist. According to the National Building Code of Canada (NBC) resonance for structures exposed to human activity can occur if the natural frequency of the structure is below 10 Hz which takes into consideration the believe by the NBC that resonance is attainable if the forcing frequency of a repetitive motion such as dancing is around half the natural frequency of the floor (Murray et al, 2003). Another important parameter is acceleration. Critical floor accelerations occur at resonance but their effect on vibration serviceability of the floor depend on human perception. This is dependent on the activity type the occupants are involved in. Acceptable acceleration limits are recommended in the NBC and the International Standards Organization (ISO 2631-2, 1989) for various occupancies such as office or residential, dining or weightlifting and rhythmic activity (Murray et al, 2003). Because the criterion by the NBC is based on the beam theory, models the floor as a single degree-of-freedom and only considers the fundamental mode of vibration, Ji et al (1994) and Ellis et al (2004) proposed an alternative criterion which entails the characterization of the load which pertains to the determination of the load model in a form of a Fourier series, evaluation of the characteristics of the floor vibration and calculation of the response of the floor to the dancing loads. Of all the design codes reviewed, only the British Standard provided the load model which can be used in the analysis of structures subjected to rhythmic loads. The UK National Annex to Eurocode 1: Part 1-1 does, however, recommend that a designer consult literature that provide rhythmic load models such as that by Ellis et al (2004). Measures that can be applied to improve the vibration serviceability of planned or existing structures include increasing the stiffness of the structure, increasing the damping, installing tuned vibration absorbers and restricting the usage of the structure (Erlina et al, 2017). Three different floor systems were studied in this research, namely, the plane truss, space frame and space grid floors and different measures were applied to evaluate their effect on the vibration behaviour of these floor systems under rhythmic loading. The results showed that increasing the number of column supports, adding extra edge supports around the floor perimeter and increasing the floor depth all improve the vibration serviceability of the floor. The results also showed that the space frame floor performed better under rhythmic loading than the plane truss and space grid floors. The space frame, however, required large members (resulting in a relatively heavy structure) to work and is complicated and costly to construct. It was therefore determined that when taking into consideration both the vibration serviceability of the structure and the ease and cost of construction that the space grid was the best structural system to employ. Physical tests need to be carried out on existing long span floors under rhythmic loads to verify the FE analysis results obtained in this study. Guidelines in design codes should also be updated to make special provision for long-span floors subjected to rhythmic loading.